Penerapan Metode Activity-Based Costing dan Penetapan Tarif pada UMKM (Studi Kasus Magnet CyberGame) - Lita Febriyanti Suherman; Rahma Nazila Muhammad (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
Magnet CyberGame is MSMEs in Internet Cafe services. Applicable internet rates are estimated by relying on fair prices prevailing in the area without calculating the costs incurred, making it difficult to measure performance in each period. The aim of this research is to compare the rate calculations based on Activity-Based Costing with the rates used before. The method used is a qualitative method with a case study on the actual data obtained from interviews, observations and documentation. The analysis used is comparative analysis, the author compares the applicable rates with the rates based on the ABC method. The results show that the Regular and VIP rates are currently still unable to meet the target of having 50% profit in every hour of each available package. This is based on the calculation of rates plus markup 50% with each difference Rp. 3,500 and Rp. 1,000. This research is expected to be considered by Magnet CyberGame and other MSMEs in the same sector for determining internet rates.